2002
DOI: 10.1038/nature01020
|View full text |Cite
|
Sign up to set email alerts
|

Curvature of clathrin-coated pits driven by epsin

Abstract: Clathrin-mediated endocytosis involves cargo selection and membrane budding into vesicles with the aid of a protein coat. Formation of invaginated pits on the plasma membrane and subsequent budding of vesicles is an energetically demanding process that involves the cooperation of clathrin with many different proteins. Here we investigate the role of the brain-enriched protein epsin 1 in this process. Epsin is targeted to areas of endocytosis by binding the membrane lipid phosphatidylinositol-4,5-bisphosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,113
5
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 944 publications
(1,171 citation statements)
references
References 27 publications
48
1,113
5
5
Order By: Relevance
“…Here we identified two new partners of Vps27p: Ent3p and Ent5p, two PtdIns(3,5)P 2 effectors required for ubiquitin-dependent protein sorting into the MVB. It has been proposed that a function of the epsin1 ENTH domain at the plasma membrane is to induce membrane curvature (Ford et al, 2002). Once bound to PtdIns(4,5)P 2 , the 8-helixfolded ENTH domain of epsin 1 rearranges and an additional ␣ helix is formed (␣0, Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we identified two new partners of Vps27p: Ent3p and Ent5p, two PtdIns(3,5)P 2 effectors required for ubiquitin-dependent protein sorting into the MVB. It has been proposed that a function of the epsin1 ENTH domain at the plasma membrane is to induce membrane curvature (Ford et al, 2002). Once bound to PtdIns(4,5)P 2 , the 8-helixfolded ENTH domain of epsin 1 rearranges and an additional ␣ helix is formed (␣0, Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was recently shown that Vps27p is directly recruited to PtdIns(3)P-containing endosomes where it binds to ubiquitinated MVB cargoes and subsequently recruits the ESCRT-I complex (Bilodeau et al, 2003;Katzmann et al, 2003). This results in sorting of ubi- (Ford et al, 2002). Once bound to PtdIns(4,5)P 2 , the 8-helixfolded ENTH domain of epsin 1 rearranges and an additional ␣ helix is formed (␣0, Figure 1).…”
mentioning
confidence: 99%
“…Ceci est bien illustré par les fréquents treillis plats de clathrine observés à la surface de nombreuses cellules [23]. Le rôle actif de certaines protéines capables de « sculpter » la membrane plasmique a été établi [24][25][26][27]. En revanche, parmi les protéines connues ayant ces propriétés, la plupart ont un rôle tardif lors de la transition, au moment où les puits de clathrine deviennent des vésicules.…”
Section: Induction Des Vésicules De Clathrine : Le Rôle Controversé Dunclassified
“…Lors d'expériences de tubulation in vitro, le domaine F-BAR de FCHo2 est capable de déformer des liposomes en tubes de diamètres allant de 130 à 18 nm selon la concentration de protéines [28]. Plusieurs autres protéines telles que l'amphi physine, SNX9, FBP17, l'endophiline et l'epsine sont impliquées dans la formation de vésicules de clathrine et ont la capacité d'induire une courbure de la membrane [25][26][27]31]. En revanche, toutes ces protéines ont un rôle plus tardif que les FCHo et n'induisent pas la nucléation des puits de clathrine.…”
Section: Comment Les Protéines Fcho Induisent-elles La Formation Des unclassified
“…Another protein, epsin, in fact plays a crucial role in inducing the curvature of the membrane. 24,26 The protein epsin has binding sites in the clathrin lattice and also directly interacts with the membrane. This dual interaction together with the dual interaction of an adaptor protein Ap180 with clathrin and the membrane (Ap180 tethers the clathrin coat to the membrane) is believed to induce the vesicle nucleation and anchor the clathrin lattice to the budding vesicle.…”
Section: Spatial Stochastic Model For Endocytotic Vesiclementioning
confidence: 99%